2022
DOI: 10.3389/fpubh.2022.859350
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Among Healthcare Workers in Asia and Africa and Its Association With Their Knowledge and Awareness: A Systematic Review and Meta-Analysis

Abstract: IntroductionThe hepatitis B virus (HBV) is a blood-borne virus that can be transmitted by percutaneous and mucocutaneous contact with infected bodily fluid. Healthcare workers (HCWs) are more exposed to HBV infection. They must have a thorough understanding of HBV infection since they can contract and spread the virus. In this study, we systematically reviewed all published evidence on the seroprevalence of Hepatitis B virus (HBV) infection among HCWs. and synthesize evidence on the association between knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Saharan Africa up to 2020 (6.81%; 95% CI 5.67-7.95) [23] and is above the prevalence found in the meta-analysis that included Asian countries, 4.0% (95% CI: 0.01-0.07) [24]. In Mozambique, although there are no national data for HBV prevalence, the HBsAg prevalence (4.7%) found in this study is similar to those recently found in Beira City among blood donors approved for donation (4.5%) [25] and in Maputo City (southern Mozambique) among pregnant women (4.0%).…”
Section: Plos Onementioning
confidence: 61%
“…Saharan Africa up to 2020 (6.81%; 95% CI 5.67-7.95) [23] and is above the prevalence found in the meta-analysis that included Asian countries, 4.0% (95% CI: 0.01-0.07) [24]. In Mozambique, although there are no national data for HBV prevalence, the HBsAg prevalence (4.7%) found in this study is similar to those recently found in Beira City among blood donors approved for donation (4.5%) [25] and in Maputo City (southern Mozambique) among pregnant women (4.0%).…”
Section: Plos Onementioning
confidence: 61%
“…Thus, Western Pacific region and sub-Saharan region account for more than 75% of the worlds chronic HBsAg carries [ 1 , 7 ]. The high prevalence of HBV in Africa, including Ghana, can be attributed to poverty and a lack of understanding about the disease [ 8 ]. Previous study by Agyemang and colleagues shows 12.3% prevalence rate of the HBV infection, as detected by HBsAg seropositivity making it one of the highest globally [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B viral infection is of public health concern (1,5).The prevalence of chronic infections was estimated to be at 296 million individuals in 2019, with an annual incidence of 1.5 million new infections (6,7). Amongst these cases, it was observed that 68% resided in Africa and Western Pacific Asia (8,9). Moreover, it has been reported that a significant proportion, ranging from 5% to 15% of individuals residing in underdeveloped nations and countries with low income are persistently infected with the hepatitis B virus (10,11).…”
Section: Introductionmentioning
confidence: 99%